Quantifying Physicochemical Properties of Honey Collected from Different Floral Sources of Islamabad and Mardan Regions - Komal Tariq; Sabir Iqbal; Muhammad Fraz Ali (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2022)
Introduction: Honeybee (Apis mellifera ) is known for pollination and honey production. There are some physicochemical properties through which the honey identifies. The current study was aimed to study the physiochemical characteristics of different honey sources collected from Islamabad and Mardan districts of Pakistan according to the prescribed international standards. Materials and Methods: This study was conducted in Honey Analysis Laboratory, Honey Bee Research Institute (HBRI), National Agriculture Research Center (NARC) Islamabad, to evaluate the physicochemical properties of honey collected from different floral sources of Islamabad and Mardan regions. The total of 12 honey samples of mellifera L. were tested. In this study 12 honey samples were collected from beekeepers of Islamabad and Mardan area. Physicochemical analysis such as moisture content, pH, electrical conductivity, free acidity, total soluble solids, density and pollen analysis were carried out. Results: showed that some of the samples have high value for moisture, pH and electrical conductivity while the other parameters were in normal range. Results of the physicochemical properties show the following range of values for moisture content (1.36-1.55%), pH (3.72-6.61), EC (0.1-1.1), acidity (10-30 meq/kg), total sugars (76.2-78.8%), density (1.23-1.46 kg/l), and pollen analysis showed multiple floral samples.